Heterodoxus spiniger (Enderlein, 1909) on domestic dogs (Canis familiaris, L. 1758) from the city of Recife, Pernambuco State, Brazil - Torres, Filipe Dantas; Figueredo, Luciana Aguiar (Brazilian Journal of Veterinary Research and Animal Science, 2007)
In the city of Recife, Pernambuco state, northeastern Brazil, domestic dogs are usually infected by ectoparasites of both veterinary and public health importance. Heterodoxus spiniger is a common dog chewing louse, which is known as an intermediate host of Dipetalonema reconditum. Despite of its wide geographical diffusion in Brazil, Heterodoxus spiniger was only recently recorded in Pernambuco. The aim of this paper was to verify the infestations by Heterodoxus spiniger on dogs from Recife. Three hundred and ten dogs were examined and 11 of these were parasitized by Heterodoxus spiniger, corresponding to a prevalence rate of 3.5%. This indicates that Heterodoxus spiniger can be found on dogs from Recife, but in low prevalence.